2002
DOI: 10.1124/jpet.102.033340
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Disposition of Resveratrol in Rats: Extent of Absorption, Glucuronidation, and Enterohepatic Recirculation Evidenced by a Linked-Rat Model

Abstract: Pharmacokinetics of trans-resveratrol in its aglycone (RES AGL )and glucuronide (RES GLU ) forms were studied following intravenous (15 mg/kg i.v.) and oral (50 mg/kg p.o.) administration of trans-resveratrol in a solution of ␤-cyclodextrin to intact rats. In addition, the enterohepatic recirculation of RES AGL and RES GLU was assessed in a linked-rat model. Multiple plasma and urine samples were collected and concentrations of RE-S AGL and RES GLU were determined using an electrospray ionization-liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
294
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(325 citation statements)
references
References 18 publications
26
294
3
Order By: Relevance
“…Much higher values of the absorptivity parameters from OPT formulation can be ascribed to the transport of drug via lymphatic pathways, in accordance with an earlier literature report (Sun et al, 2011). The existence of enterohepatic circulation and extensive first-pass metabolism by CYP3A4 in liver has been documented as the plausible cause for low oral bioavailability of t-RVT (Marier et al, 2002;Amri et al, 2012). Marked enhancement in the effective permeability, a direct measure of absorption across the intestine (Bandyopadhyay et al, 2012), of the SNEDDS clearly demonstrates that the OPT formulation was able to augment drug absorption in rat.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Much higher values of the absorptivity parameters from OPT formulation can be ascribed to the transport of drug via lymphatic pathways, in accordance with an earlier literature report (Sun et al, 2011). The existence of enterohepatic circulation and extensive first-pass metabolism by CYP3A4 in liver has been documented as the plausible cause for low oral bioavailability of t-RVT (Marier et al, 2002;Amri et al, 2012). Marked enhancement in the effective permeability, a direct measure of absorption across the intestine (Bandyopadhyay et al, 2012), of the SNEDDS clearly demonstrates that the OPT formulation was able to augment drug absorption in rat.…”
Section: Discussionsupporting
confidence: 74%
“…Second peak at 2 h indicates enterohepatic recirculation of the drug that has been well documented and enterohepatic recirculation is susceptible to circadian variation (Almeida et al, 2009) (as is evident from Figure 4 where two peaks of C max and T max were observed). A major portion of the bile acids secreted are reabsorbed from the intestines and returned via the portal circulation to the liver, thus completing the enterohepatic cycle (Marier et al, 2002). The parent compound and its conjugated metabolite undergo enterohepatic recirculation, resulting in multiple peaks in the plasma concentration-time profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy between resveratrol and DMU 212 in concentration achieved in the small intestine and colon may be a corollary of their differential metabolic susceptibilities. The lower availability of resveratrol compared to DMU 212 may be the consequence of the high propensity of resveratrol to undergo conjugation reactions catalysed by enzymes (De Santi et al, 2000;Kuhnle et al, 2000;Marier et al, 2002), which are abundantly present in the gut (Eisenhofer et al, 1999). In contrast, on the basis of the fact that activities of oxidising enzymes in the gut are much lower than in the liver (Doherty and Charman, 2002), the ability of the gut mucosa to O-demethylate or hydroxylate DMU 212 is arguably much lower than its ability to biotransform resveratrol by conjugation.…”
Section: Discussionmentioning
confidence: 99%
“…As is the case with many polyphenols with putative cancer chemopreventive properties, the systemic bioavailability of resveratrol is probably poor. This notion is borne out by studies in mice, rats and dogs, which suggest consistently that resveratrol is well absorbed but avidly glucuronidated and sulphated both in the liver and in intestinal epithelial cells (Asensi et al, 2002;Juan et al, 2002;Marier et al, 2002). One study in humans also hints at a poor bioavailability of resveratrol (Goldberg et al, 2003).…”
mentioning
confidence: 99%